JOHNMASEFIELD: A STUDY - Vikash kumar (International Journal of Multidisciplinary Research and Studies, 2021)
In 1958, John Masefield made the observation that out of three hundred million readers of English, three read his work and four criticized it. In 1978, a later Poet Laureate named John Betjeman made the observation that "Sea-Fever" and "Cargoes" would be "remembered as long as the language lasts." In 1958, John Masefield made the observation that out of three hundred million readers of English, three read his work and four criticized it. These instances represent two perspectives during the collapse of a reputation for Masefield, who was once a best-selling author and a publishing sensation. During this time period, Masefield’s reputation was falling. He received accolades from the academic community as well as honors on a global scale. The downward trend may have reached its end as of today. An important character in the history of literature is only remembered now in old-fashioned poetry collections. Masefield’s prolific productivity, Edwardian multiplicity, and success in the past all work against him now. His books are, for the most part, no longer in print, and academic circles pay him little mind. It was not necessary for it to occur. Masefield was a writer who, notably in the 1920s, made an effort to reinvent himself. However, in the process of repressing (or trying to hide) his work, he committed a number of mistakes.